Application of radar signal processing and image display algorithm based on computer hardware system in intelligence processing - Zhang, Na; Xie, Hongsen; Li, Jinjie; Chen, Hong (Microprocessors and microsystems, 2021)
Hardware system based radar signal detection, specific progress and current limitations. As indicated by the radar signal's characteristics, the radar signal's plan and arrangement are introduced with the irregularities and favorable conditions of the mirror mark. The radar signal's multidisciplinary preparatory invention is equipped with a versatile radar signal cycle, beat signal administration, computerized sifting signal mode, and Doppler strategy indicating nuances. An image display algorithm based on the radar signal's transmission cycle is extracted, which includes the transmission stages of the radar signal, the factors affecting the radar signal transmission and the radar data screening. Planning technology for radar signal and related signal characteristics will be evaluated to improve implementation. Radar signal calibration strategy and related impact factors are additionally isolated and described. Radar signal handling is described in detail, including the Innovation Multidisciplinary Innovation compound. Versatile radar signal cycle beat pressure executives and computerized separating Doppler strategy are very effective specialized techniques with interesting features. Finally, the difficulties of future testing methods and the progress of radar signals are proposed.